If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3 = 7x + -15 Reorder the terms: 3 + x = 7x + -15 Reorder the terms: 3 + x = -15 + 7x Solving 3 + x = -15 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 3 + x + -7x = -15 + 7x + -7x Combine like terms: x + -7x = -6x 3 + -6x = -15 + 7x + -7x Combine like terms: 7x + -7x = 0 3 + -6x = -15 + 0 3 + -6x = -15 Add '-3' to each side of the equation. 3 + -3 + -6x = -15 + -3 Combine like terms: 3 + -3 = 0 0 + -6x = -15 + -3 -6x = -15 + -3 Combine like terms: -15 + -3 = -18 -6x = -18 Divide each side by '-6'. x = 3 Simplifying x = 3
| 9=4(3k-4) | | 1.1x+3.2+0.2x-1.4=0 | | 39.34+2.56=56.03x | | 45x-33=87 | | 3(g-21)=2(10+g) | | 34x=32 | | 69=h+2h+(h-7) | | 66-34=x | | 10000+5.75x-25y= | | 8x+6(x-2)=-5(x-4)-x+8 | | (m-2)(m+2)=64 | | 5b-(4b+2)=14-2b+11 | | m^2-4m-62=-2 | | 10(-x+2)=-3(7x+2) | | (y-7)=2(x+2) | | 14x+(2-x)=6(2x-1) | | 7(x+5)+3=6(x+5) | | 4v-2=30 | | 40+6=n-3 | | Y-5=4(x+6) | | 2=10c-4(2-9) | | y=-2x^2+16x-34 | | y=-2x^2+16-34 | | 9(x+3)=4x-4 | | 18=9 | | 10y-2y=646 | | -26+x+2=16 | | .5x+5=7+1 | | X+2=4x-4-5x+2 | | 6x-14-4x=28 | | 3h(h+1)=3h^3 | | x^4-4x^3-10x^2+28x-15=0 |